DINAMIKA MODEL EPIDEMIK SVIR TERHADAP PENYEBARAN PENYAKIT CAMPAK DENGAN STRATEGI VAKSINASI KONTINU - Sahni, Anis; Wangkok Yohanis Marente, Tonaas Kabul; -, Suwandi (Universitas Pasir Pengaraian, 2015)
Measles is a infectious disease caused by a virus that could be solved one of them with the process of vaccination. This model is based on Xianning Liu 2007), Marentek (2011) and a adding again the assumption that vaccinated individuals have the possibility to stay h healthy but vulnerable to disease, because immunity is only obtained during the process of vaccination alone. SVIR epidemic models, there are two fixed points are points remain free of disease and endemic fixed. If the basic reproduction number is equal to one will obtain a minimum level of vaccination. To make it easier to observe the dynamics of the system as well as the influence of continuous vaccination, then used computer simulations using the software Mathematica 7.0 to give explicit parameters and in accordance with the measles